Study of microstructure and ageing characteristic of aluminium alloy reinforced with glass particulates - Hadipramana, Josef (Universiti Malaysia Perlis, 2010)
Study on microstructure and ageing characteristics has been done on the aluminium alloy reinforced with glass particulates. Aluminium - 4 wt. % copper composites were produced by powder metallurgy technique. Composition of 0, 5, 10, 15, 20 and 25 wt. % glass particulates was mixed into aluminium - 4 wt. % copper alloy. All composites were fabricated by mixing, pressing and sintering. The sintering was performed at 548º C. Ageing of the composites was done by solution heat treatment at 510º C followed by quenched rapidly into cool water and artificial aged for 10 hours at 160º C. XRD and DSC analysis showed the precipitation formation in unreinforced and reinforced Al - 4 wt. % Cu alloy. Unreinforced Al – 4 wt. % Cu alloy showed the precipitation of Al2Cu during sintering, but after solution treatment Al2Cu detected as small peak by XRD. It is indicated that Al2Cu did not completely dissolved. In addition, reinforced Al - 4 wt. % Cu alloy with glass particulates showed precipitation of Al2Cu during sintering but after solution treatment, undissolved precipitates were observed at the interface between glass particulates and the aluminium matrix. It showed incomplete dissolution. Ageing has influenced the precipitation formation in the composite because Al2Cu indicated higher intensity of XRD pattern as compared to the composite without ageing. The microstructures of the composites showed that the glass particulates were homogenously distributed in the matrix. However, glass particulates with the composition of 10, 15, 20 and 25 wt. % were found segregated near copper. The formation of AlCu and Al2Cu phases was interfered by the presence of glass particulates. The aluminium oxide layer in the matrix is produced between aluminium, copper and glass particulate. It is harder than matrix that indicated by micro cracks in aluminium oxide layer and at interface between aluminium oxide layer and aluminium. Furthermore, it was found an increase in the hardness of matrix and that is found responsible for hardening mechanism. After sintering, hardness value indicated that the composite with 25 wt. % glass had highest hardness i.e. 34.87 HV than unreinforced aluminum alloy i.e. 15.83 HV. The hardness value increased with increasing the glass composition in the aluminium alloy. Ageing kinetic of the composites was slower than unreinfoced aluminium alloy. The slow ageing kinetic was expected due to the presence of glass particulates which disturbed precipitate formation of aluminium-copper and delay the G.P. zone formation.